Butik Citranggun Sdn. Bhd. / Nur Azwa Ibrahim ... [et al.] - Ibrahim, Nur Azwa; Baharudin, Siti Mariah; Sulieman, Norhuda (Faculty of Communication and Media Studies, 2004)
Butik Citra Anggun Sdn. Bhd is set up with its main activity to provide tailoring service to the customers. This business is fit in our environment as the tailoring industry is always expanded. People need cloth in their daily life. They will ask for a tailor to make specified sized clothes, especially for special occasions or events. In addition, the world of fashion is always changing, and therefore both men and women will seek for a new fashion. Butik Citra Anggun will be located at No 28 Jalan Tiga Belas, Pusat Bandar Puchong, Selangor. Our premise is at the centre of Puchong town. It is near TESCO Hypermarket, IOI Mall and Giant Hypermarket and also surrounded by many residential areas. Moreover we sure this is strategic place to our business as there are not many tailoring service that are set up commercially. We choose the tailoring service because the industry will never fade away by time and there will always demand for it. Although there is a big market and supply for ready made clothes, the tastes and preferences for everybody is different. With the existence of Butik Citra Anggun, our customers can fulfill their needs and wants by subscribing our tailoring service. Besides, we also provide ready made traditional clothes which are sew by our tailors as the additional choice for the customers. Our target market is the employed woman of Pusat Bandar Puchong.